Peran Perempuan terhadap Pengembangan Usaha Kecil Dalam Mendukung Kota Ambon Sebagai Kota Kreatif (Studi Kasus: Negeri Rutong, Kec. Leitimur Selatan, Kota Ambon) - Huwae, Silvana Yoanda; Nurhaeny, Andiah; Ode Sitti Jurianti Aswad, Wa (Journal of Urban Planning Studies, 2024)
The aim of this research is to explain the role of women in small business development in supporting Ambon City as a creative city. The research method used in this research is a qualitative descriptive research method with SWOT analysis techniques. Based on the identification results, the role of women in Rutong State has a role in the stages of providing business capital, then also in the production process stages, distribution stages of business products and marketing stages of business products. To develop the Women's Group and Rutong Country based on MSME activities, SWOT analysis is used in formulating strategies and also looks at the Internal Aspect, namely the Strengths and Weaknesses, and the External Aspect, namely Opportunities and Threats that come from outside. Therefore, the strategy formulated is the right strategy that can develop Women's Groups in MSME activities and develop Rutong State based on MSME activities